The Mexican Non-toxic Jatropha curcas L., Food Resource or Biofuel? - Valdes-Rodriguez, Ofelia Andrea; Sanchez-Sanchez, Odilon; Perez-Vazquez, Arturo; Caplan, Joshua (Ethnobotany Research and Applications, 2013)
Jatropha curcas L. is a promising natural resource which has been promoted globally for biodiesel production by policy makers and researchers in tropical and subtropical countries. However, both J. curcas seeds and oil have been found to be toxic to humans and domestic animals when consumed. A non-toxic genotype of J. curcas has been reported from some rural communities in southern Mexico, and is suitable for human consumption. This non-toxic germplasm has been used in traditional Totonacan cuisine in Mexico. However, increasing demand for J. curcas to be used in biofuel production is exerting pressure on the non-toxic genotype. In this work we analyze the possible origins and dispersal of non-toxic Jatropha by the Totonaca culture; the traditional uses of J. curcas seeds as a food; its status with respect to the Mexican commercial forestry regulations; and the risks associated with the demands of biofuels on this Mexican germplasm. <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} > <! [endif] > Jatropha curcas is a promising natural resource which has been promoted for biodiesel production by policy makers and researchers in tropical and subtropical countries globally. However, both J. curcas seeds and oil have been found to be toxic to humans and domestic animals when consumed. A non-toxic genotype of J. curcas has been reported from some communities in southern Mexico, and is suitable for human consumption. This non-toxic germplasm has been used traditionally in Mexico to prepare a variety of dishes. However, increasing demand for J. curcas to be used in biofuel production is exerting pressure on the non-toxic genotype. In this work we analyze the possible origins and dispersal of non-toxic Jatropha by the Totonaca culture; the traditional uses of J. curcas seeds as a food; its status with respect to the Mexican commercial forestry regulations; and the risks associated with the demands of biofuels on this Mexican germplasm.<-->